Slumdog millionaire : a novel - Swarup, Vikas (London : Black Swan, 2009)
After winning India's biggest quiz show, Ram Mohammad Thomas is put in jail as authorities question how a poor orphan who has never gone to school could win such a contest.
"Originally published as Q & A.
Adult.
Adult
Keywords: Billionaires -- Fiction; Poor -- Fiction; Waiters -- Fiction; Poor -- Fiction; Rich -- Fiction; Waiters and waitresses -- Fiction; Bombay (India) -- Fiction; Bombay (India) -- Fiction